FEATURES OF STRATEGIC DEVELOPMENT MANAGEMENT OF CONSTRUCTION INDUSTRY ENTERPRISES IN CRISIS CONDITIONS (Development Service Industry Management, 2023)
The article reveals aspects of the relevance of safe and effective functional and economic development, development and development of its industry in conditions of war, crisis and instability. A methodologically based strategic management system for the development of construction industry enterprises in crisis conditions.A methodology for researching the problems of managing the strategic development of construction industry enterprises has been developed, which consists of three blocks: 1) identification of challenges and threats to the functioning and development of domestic construction industry enterprises in conditions of instability; 2) analysis of the problems of functioning and development of enterprises in the construction industry on the example of one of the construction enterprises; 3) determination of directions and means of managing the strategic development of enterprises in the construction industry in crisis conditions.It has been proven that the key challenges and threats to the functioning of construction enterprises of Ukraine in crisis conditions are formed by such components of their stable functioning and development as financial and economic, material and resource, technological and personnel. It has been identified that the influence of negative factors along these vectors leads to the washout of working capital and the increase in the cost of raising capital, the freezing of a number of objects, the increase in the price of construction materials and services, the suspension of cooperation programs within industrial clusters, the washout of human resources as a result of large-scale external and internal migration processes, growing shortage of qualified personnel. According to the results of the analysis of the problems of the functioning and development of enterprises in the construction industry of Ukraine, using the example of one of the construction enterprises of the western region of the country, it was established that the most tangible are such internal difficulties (problems), as a low level of financial condition, in particular liquidity and solvency, deterioration of the technical and technological component of construction -technological processes, insufficient adaptability to requirements and changes in state regulation. It has been proven that in conditions of a critically high level of instability in order to ensure effective management of the strategic development of domestic enterprises in the construction industry, it is necessary to implement a set of measures both on the part of the enterprises themselves and the state. The combination of these steps is coordinated within the framework of the matrix of means of managing the strategic development of enterprises of the construction industry of Ukraine in conditions of instability, which are differentiated by strategic stages: (1) full-scale war, (2) post-war reconstruction of the national economy of Ukraine, (3) strategic development of our state.
Keywords: management; strategic management; enterprise development; construction; construction industry; strategic development; war